Reproductive cycle of the swimming crab Portunus spinimanus Latreille (Crustacea, Decapoda, Brachyura) from Ubatuba, São Paulo, Brazil - Santos, Sandro; Negreiros-Fransozo, Maria Lucia [UNESP] (Sociedade Brasileira de Zoologia, 1999)
This study analyses some reproductive aspects of Portunus spinimanus Latreille, 1819, a crab usually commercialized in Ubatuba region. Monthly otter-trawl collections were taken for two years along the northern coast of São Paulo State, Brazil. The reproductive period was studied based on the frequency of ovigerous females in the population along the year; the frequency of physiologically mature swimming crabs and the type of spawn. The condition of development of ovigerous females ovary was associated with the stage of eggs development. This species presents continuous reproduction in Ubatuba region and total spawn, but with successive broods, which suggests a multiple spawn during the reproduction period.
Keywords: Portunus spinimanus; reproduction; spawn; Brazilian coast